Financial assessment of incremental seismic retrofitting of Nepali stone-masonry buildings. (15th June 2021) - Giordano, Nicola; Norris, Alastair; Manandhar, Vibek; Shrestha, Liva; Paudel, Dev R.; Quinn, Natalie; Rees, Elizabeth; Shrestha, Hima; Marasini, Narayan P.; Prajapati, Rajani; Guragain, Ramesh; De Luca, Flavia; et al.
Abstract: Despite its critical location, right on top of the Main Himalayan Thrust, the building stock of Nepal is mainly constituted by highly vulnerable non-engineered unreinforced masonry (URM) buildings. Most of them were realized with traditional construction techniques and locally available materials like field stones and mud mortar. The empirical evidence from historical earthquakes has shown that these buildings have very limited seismic capacity. On the contrary, if adequate retrofitting interventions are implemented, their seismic performance can improve substantially. Unfortunately, the upfront investment required by retrofitting remains an issue since it is considered too high and not associated with an immediate and tangible benefit. This prevents building owners and investors from retrofitting properties as preparedness measure. Starting from these considerations, this work presents an incremental approach for the implementation of retrofitting so that the total investment is spread over time in a gradual and cost-effective way. In details, two government-approved retrofitting techniques for Nepali stone in mud mortar masonry (SMM) buildings are broken down into phases and analysed from an engineering and financial perspective. A probabilistic cost-benefit analysis of each phase is carried out to quantify the return on investment and the payback time of seismic enhancement. Results indicate that retrofitting is a financially advantageous investment since the reduction in future earthquake-induced loss exceeds the upfront cost of the intervention. Additionally, the incremental approach allows more flexibility in implementing effective risk management actions at regional and national scale.